Exploring the Ratib Tolak Bala Ritual in Langkat, North Sumatra: Analysis of Living Qur’an - Muttaqin, Zainul; Jamil, Jamil (Program Studi Ilmu Al-Qur`an dan Tafsir, Fakultas Ushuluddin, UIN Sunan Kudus, 2024)
This study aims to examine the phenomenon of the Ratib Tolak Bala ritual in the Naqayabandiyah Khalidiyah Tariqah in Besilam Village, Babussalam, Langkat, North Sumatra. This research is a field study with a qualitative descriptive method. The research subjects include community leaders, traditional figures, and religious figures. Data collection was done directly from primary sources through observation and interviews. The results show that the Ratib Tolak Bala ritual is a series of dhikr activities performed by a group of people after the Isha prayer, usually at night, collectively along the roads of Besilam Village. Its purpose is to repel and reject disasters and threats, solely as a form of seeking protection and safety from Allah SWT. The Ratib Tolak Bala ritual has three elements of value: cultural preservation, spiritual value, and social cohesion.